2005
DOI: 10.1177/0020872805050492
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of stress among mental health social workers

Abstract: English In the UK mental health social workers reported role conflict, role ambiguity and fulfilling statutory responsibilities as possible sources of stress. Burnout was related to workload, degree of involvement with patients, lack of social support and role conflict. Further work, which investigates coping strategies and stress management interventions, is recommended. French Au Royaume-Uni, les travailleurs sociaux en santé mentale signalent un problème de conflit de rôle, de l’ambiguïté de rôle et des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 17 publications
2
57
1
6
Order By: Relevance
“…Burnout refers primarily to states of occupational stress prevalent among human services professionals (Bargal, 1984). Social workers are considered to be at risk of burnout and several studies have focused specifically on burnout in this group (Abdallah, 2009;Abu-Bader, 2000;Cherniss, 1980;Coyle et al, 2005;Edelwich and Brodsky, 1980;Haj-Yahia et al, 2000;Jayaratne et al, 1983;Lloyd et al, 2002;Pines and Aronson, 1988;Tam and Mong, 2005). Many of these studies have found that burnout is associated with a lack of autonomy at work (LeCroy and Rank, 1987); excessive bureaucratization (Arches, 1991); role ambiguity (Himle et al, 1987); low professional self-esteem (LeCroy and Rank, 1987); the lack of social support (Kim and Lee, 2009); or the intensity of contact with users (Streepy, 1981).…”
Section: Burnout In Social Workmentioning
confidence: 99%
“…Burnout refers primarily to states of occupational stress prevalent among human services professionals (Bargal, 1984). Social workers are considered to be at risk of burnout and several studies have focused specifically on burnout in this group (Abdallah, 2009;Abu-Bader, 2000;Cherniss, 1980;Coyle et al, 2005;Edelwich and Brodsky, 1980;Haj-Yahia et al, 2000;Jayaratne et al, 1983;Lloyd et al, 2002;Pines and Aronson, 1988;Tam and Mong, 2005). Many of these studies have found that burnout is associated with a lack of autonomy at work (LeCroy and Rank, 1987); excessive bureaucratization (Arches, 1991); role ambiguity (Himle et al, 1987); low professional self-esteem (LeCroy and Rank, 1987); the lack of social support (Kim and Lee, 2009); or the intensity of contact with users (Streepy, 1981).…”
Section: Burnout In Social Workmentioning
confidence: 99%
“…Por fi m, sobre as limitações deste estudo, a primeira é que os resultados encontrados não podem ser generalizados para outros serviços semelhantes, uma vez que se tratou de um diagnóstico de um serviço em específi co. Outra limitação foi o estudo não ter explorado os fatores moderadores do estresse como fi zeram Coyle et al (2005), pois estes não integram o instrumento aqui utilizado. Futuros estudos devem avaliar em que medida as intervenções de gestão, potencialmente capazes de "humanizar o serviço", atuam como fatores moderadores do estresse na equipe.…”
Section: Considerações Fi Nais E Limitações Do Estudounclassified
“…O que tem sido afi rmado sobre os riscos ao bem--estar e à saúde dos trabalhadores da saúde em geral, também se aplica fortemente, e com especifi cidades, aos trabalhadores de saúde mental -por exemplo, a maior exposição ao estresse ocupacional (Coyle, Edwards, Hannigan, Fothergill & Burnard, 2005;Fensterseifer, 1999;Ramminger, 2002;Rego, 2000;Santos & Cardoso, 2010).…”
unclassified
“…180). Reviews of the experience of stress in other caring professions confirm that workload is likely to be a relevant stressor (Coyle, Edwards, Hannigan, Fothergill, & Burnard, 2005;Edwards, Burnard, Coyle, Fothergill, & Hannigan, 2000).…”
Section: Stress and Bumout 13mentioning
confidence: 99%